Implementation of Psychodynamic Multifamily Groups for Severe Mental Illness: A Recovery-Oriented Approach - Maone, Antonio; D'Avanzo, Barbara; Russo, Federico; Esposito, Rita Maria; Goldos, Bozena Lucyna; Antonucci, Alessandro; Ducci, Giuseppe; Narracci, Andrea (Frontiers in Psychiatry, 2021)
Background: Among Family-Based Services for the treatment of severe mental illnesses, multi-family models gained particular attention, given the potential usefulness of mutual feed-back, motivation and encouragement among families. Methods: The Psychodynamic Multi-Family Group Model has been proposed since 1997 in some Community Mental Health Services in Rome. Since 2011 multifamily groups are held weekly in all the six Districts of the Department of Mental Health that serves a population of more than one million people, and data have been collected since 2015 in three Districts. A total of 794 individuals attended the meetings in the period 2015–2019. Results: Eighty-six percent of those who started, attended more than one meeting. The mean of occurrences of participation among patients was 18.6, among mothers 25.6 and among fathers 21.6. The 794 participants belonged to 439 family units, among which 180 comprised only the patient, 76 only parent(s) or other close person(s), and 183 comprised parent(s) or close person(s) with the patient. Patients participating alone were older than those of families who participated as a whole. Families including the patient showed the longest duration of attendance and the highest prevalence of a diagnosis of schizophrenia in the index patient. Families who had been attending the multifamily groups since a long time maintained a high rate of attendance. Conclusions: Multifamily groups represent a setting where patients can meet with other people and professionals in a free still structured way, and with not strictly therapeutic objectives. The high number of patients who attended alone suggests that such participation corresponds to a self-perceived need of open and free setting facilitating sharing of problems and solutions. The good tenure of the interventions, the high participation, and the feasibility in the long-term suggest that multifamily groups can be implemented in the mental health services of a large city, are sustainable over many years, and can represent a valuable resource for many patients and families.